2022
DOI: 10.3390/molecules27051665
|View full text |Cite
|
Sign up to set email alerts
|

Development of Improved High-Performance Liquid Chromatography Method for the Determination of Residual Caprylic Acid in Formulations of Human Immunoglobulins

Abstract: Quality control of human immunoglobulin formulations produced by caprylic acid precipitation necessitates a simple, rapid, and accurate method for determination of residual caprylic acid. A high-performance liquid chromatography method for that purpose was developed and validated. The method involves depletion of immunoglobulins, the major interfering components that produce high background noise, by precipitation with acetonitrile (1:1, v/v). Chromatographic analysis of caprylic acid, preserved in supernatant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Prior work introduced DARQ as a simple mix-and-read assay for the quantification of therapeutic monoclonal antibodies Trastuzumab and Adalimumabrespectively used in fighting breast cancer and rheumatoid arthritisin bioprocess fluids . Our results showed that DARQ technology is endowed with numerous advantages compared to ELISA, BLI, and SPR assays (Table S1), chiefly, high reproducibility, speed and ease of execution (mix-and-read), flexibility, robustness, and low cost of goods.…”
Section: Introductionmentioning
confidence: 86%
“…Prior work introduced DARQ as a simple mix-and-read assay for the quantification of therapeutic monoclonal antibodies Trastuzumab and Adalimumabrespectively used in fighting breast cancer and rheumatoid arthritisin bioprocess fluids . Our results showed that DARQ technology is endowed with numerous advantages compared to ELISA, BLI, and SPR assays (Table S1), chiefly, high reproducibility, speed and ease of execution (mix-and-read), flexibility, robustness, and low cost of goods.…”
Section: Introductionmentioning
confidence: 86%
“…Quantification of residual caprylic acid was determined by the validated HPLC method ( 26 ). Briefly, HPLC analysis was performed on RP C18 column (2.1 × 150 mm) (Shimadzu, Japan) with 0.05% TFA in water : ACN = 50 : 50 ( V / V ) as a mobile phase in isocratic mode at a flow rate of 0.2 mL min -1 on a Shimadzu HPLC system (Shimadzu, Japan).…”
Section: Methodsmentioning
confidence: 99%